Analisis Pertumbuhan Pajak Kendaraan Bermotor dan Bea Balik Nama Kendaraan Bermotor Serta Kontribusinya terhadap Pajak Daerah di Provinsi Kalimantan Selatan - Risdiani, Sovia (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aimed to determine the rate of growth, level of contribution, level of effectiveness, and trends of motor vehicle taxes and motor vehicle name transfer fees to local taxes in the province of South Kalimantan. This research uses a descriptive quantitative analysis method; the data used is secondary data obtained from digital files available from the Regional Finance Agency and the official website of the Central Statistics Agency of South Kalimantan Province, which is accessed through the website. The results of this study are the average motor vehicle tax growth rate of 11% and the transfer fee of motor vehicle names by 6%. The contribution rate of motor vehicle tax is 24.71% on average, and the transfer of motor vehicle name transfer fee is 22.75%. The effectiveness of motorized vehicle taxes is, on average, 100%, and the transfer fee for motorized vehicles is 99.3%. Then the trend method that is good for both taxes is the quadratic trend method.